The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/ac8003242
|View full text |Cite
|
Sign up to set email alerts
|

Biarsenical−Tetracysteine Motif as a Fluorescent Tag for Detection in Capillary Electrophoresis

Abstract: Biarsenical dyes complexed to tetracysteine motifs have proven to be highly useful fluorescent dyes in labeling specific cellular proteins for microscopic imaging. Their many advantages include membrane permeability, relatively small size, stoichiometric labeling, high affinity, and an assortment of excitation/emission wavelengths. The goal of the current study was to determine whether the biarsenical labeling scheme could be extended to fluorescent detection of analytes in capillary electrophoresis. Recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…35,36 A detailed description of the custom-built system can be found in the Supporting Information. Fused silica capillaries [30 μm inner diameter, 360 μm outer diameter (Polymicro Technologies, Phoenix, AZ)] had a total length of 38 cm and an effective length of 21.5 cm.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…35,36 A detailed description of the custom-built system can be found in the Supporting Information. Fused silica capillaries [30 μm inner diameter, 360 μm outer diameter (Polymicro Technologies, Phoenix, AZ)] had a total length of 38 cm and an effective length of 21.5 cm.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Detection of TC‐labeled peptides and proteins can be achieved by micellar electrokinetic chromatography (MEKC)—a capillary electrophoresis system with laser‐induced fluorescence (LIF) detection. This setup allowed detection of as little as 3×10 −20 moles of a FlAsH–FLNCCPGCCMEP complex 142. In another study, capillary zone electrophoresis (CZE) with LIF detection was reported to detect 6×10 −12 mol of the E. coli FabI protein 139…”
Section: Application In Biotechnology and Analytical Biochemistrymentioning
confidence: 99%
“…The biarsenical labeling was extended to fluorescent detection of analytes in CE 71. Recombinant protein or synthesized peptides containing the optimized tetracysteine motif “‐C‐C‐P‐G‐C‐C‐” were labeled with the biarsenical dyes and then analyzed by MECC.…”
Section: Detection Schemes and Approachesmentioning
confidence: 99%